Mencari Hidup Dengan Beternak Sapi : Studi Antropologi Gender - Damayanti, Hana; Laxmi, Laxmi (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research aims to find out and describe how family members in Mulyasari Village, Mowila District, South Konawe Regency divide tasks and functions in the household. The informants for this research were seven people, consisting of women or hpusewives, and one person as the key informant, namely the Village Head as the main village figure. Data collection in this research was involved observation and in-depth interviews. The result of this research show that the division of tasks, roles and functions in the household is carried out according to their respective roles, however, women or housewives play the main oe important role in the process of activities both in raising cows and doin household work.